"We shouldn't waste a good crisis": the lived experience of working on the frontline through the first surge (and beyond) of COVID-19 in the UK and Ireland. Issue 2 (1st February 2022) - Kinsella, Elaine L.; Hughes, Samantha; Lemon, Sarah; Stonebridge, Natasha; Sumner, Rachel C.
Abstract: Objective: Frontline workers have shown extraordinary resilience and sustained efforts since the outbreak of COVID-19. The present study used semi-structured interviews with 38 frontline workers in the UK and Ireland to explore the psychological impact of working through COVID-19. Design: The qualitative data were analysed systematically using thematic analysis. Results: Four themes were interpreted: 1) ) " I've stopped turning the telly on. I've had to because the news was making me ill": An ecosystem of influence; 2) "Dead, dead, dead": The emotional and psychological toll: 3) " It's shone a light on what we're failing on as well" : Injustices, hierarchies and heroes: and 4) " I definitely think COVID happened for a reason to stop us in our tracks and to slow us down": Unexpected positives. Conclusion: This research offers insights into how frontline workers make sense of their experiences during periods of enormous societal and occupational stress. The learnings generated have relevance for government and organisational policy-makers who have opportunities to shape future conditions for frontline workers.